Association of Oral Pre-Malignant Lesions with the Consumption of Tobacco: A Cross-sectional Observational Study - Chinmay Jani; Arpita Joshi; Kushboo Jain; Kanisha Mittal; Harshal Jadav; Divyesh Jetpariya; Omar Al Omari; Harpreet Singh; Umit Tapan; D. V. Bala (Issues and Development in Health Research Vol. 5, 2021)
Background: Tobacco use is a public health problem globally. It can be consumed by chewing and/or smoking amongst various other ways. It can not only lead to various cancers but can also cause a variety of oral pre-malignant lesions (OPML). These include, oral sub-mucous fibrosis (OSMF), tobacco pouch keratosis (TPK), leukoplakia, erythroplakia, and smoker’s palate. The primary aim of this study was to determine the prevalence of tobacco use in workers at high risk of tobacco consumption and addiction and its association with the oral pre-malignant lesions Methodology: A cross-sectional observational study of workers working in four different industries of Ahmedabad and Gandhinagar was undertaken from March 2014 to October 2014. Out of 909 workers surveyed regarding their current or former tobacco consumption, 28 (3%) were females. Oral examination was done for detecting pre-malignant lesions. The oral cavity findings were evaluated based on tobacco habits, and statistical analysis was performed to determine the significance of the relationships discovered between tobacco usage and lesions. Result: Out of 909 participants, 881 were males. Out of 28 females only one had former tobacco chewing history. To remove the gender bias, only males were included in further analysis. Out of 881 male workers 537 (60.9%) consumed tobacco; out of which, 360 (40.9%) were consumers of smokeless tobacco (SLT), and 141 (16%) were smokers. OPML were present in around 52% of the study population exposed to tobacco in the form of smoking or chewing as compared to 2.6% of those without exposure. [Odds ratio 40.58 (20.37 – 80.87)]. The odds of having OPML still remained high even after quitting for 6 months. [17.70 (8.25-38.01)]. However, the risk was significantly reduced by 56% in these former consumers [Odds ratio 0.44 (0.28-0.67)]. Out of the 360 tobacco chewers, 43% had oral lesions, compared to merely 2.6% of workers without an addiction having oral lesions. [Odds ratio 28.14 (14.05 – 56.34)]. A total of 23% of current smokers had smoker’s palate, whereas non-addicted workers did not have this lesion. Conclusion: Tobacco consumption in any form is hazardous and causes various kinds of oral premalignant lesions. Betel quid exposure causes a more harmful effect that goes unnoticed. Even though tobacco consumption has a long-lasting impact, its cessation can lead to significant risk reduction in having OPML. Awareness should be created about various lesions, and specific steps, should be taken for early diagnosis and treatment.